PROPOSTA DE DESENVOLVIMENTO DE PEÇAS PRÉ-MOLDADAS DE CONCRETO ASFÁLTICO E SUA AVALIAÇÃO DE DESEMPENHO QUANTO ÀS TENSÕES CISALHANTES - Joaquim, Douglas de Oliveira (2019)
Precast Asphalt Concrete Parts (PPCA) are known around the world for the advantages of flexible handling, storage and simplified application over conventional asphalt pavement. Due to its limited research, the mechanical characteristics of the PPCA were e